1966
DOI: 10.1901/jeab.1966.9-1
|View full text |Cite
|
Sign up to set email alerts
|

SOME DISCRIMINATIVE PROPERTIES OF FIXED RATIO PERFORMANCE IN THE PIGEON1

Abstract: The discriminative control over a spatial choice response exercised by prior behavior was studied using a procedure involving discrete exposures to a two-member chained schedule. The initial member (red key) was either a smaller or larger fixed ratio (Mix FR:FR), the completion of which produced, after a 1-sec delay, two white response keys. If the larger FR had been completed as the initial chain member, a single peck on the right white key was reinforced; after the smaller FR, a peck on the left white key wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
2

Year Published

1968
1968
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 17 publications
(14 reference statements)
3
55
0
2
Order By: Relevance
“…The first session during which all 10 durations were presented can be considered to be a generalization or transfer task, with the exception that the reinforcement contingencies remained in effect (Honig, 1965;Pliskoff and Goldiamond, 1966;Risley, 1964). Long responding for each duration is presented in exhibited predominantly long responses, the transition of 50% long responses occurring between the 3-and 4-sec durations for Birds 7 and 8 and between the 2-and 3-sec durations for Bird 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first session during which all 10 durations were presented can be considered to be a generalization or transfer task, with the exception that the reinforcement contingencies remained in effect (Honig, 1965;Pliskoff and Goldiamond, 1966;Risley, 1964). Long responding for each duration is presented in exhibited predominantly long responses, the transition of 50% long responses occurring between the 3-and 4-sec durations for Birds 7 and 8 and between the 2-and 3-sec durations for Bird 9.…”
Section: Resultsmentioning
confidence: 99%
“…Two different training procedures were used to introduce the 10 stimulus durations. In the first procedure, all 10 durations occurred in each session, but the side key for the inappropriate choice was initially dark, then gradually made brighter over several sessions (Pliskoff and Goldiamond, 1966 …”
Section: Experiments I: Establishment Of Discrimination Of Stimulus Dumentioning
confidence: 99%
“…First, the above-mentioned studies of sample-specific responses used only two distinct response requirements (e.g., DRL and FR), thus precluding the possibility of observing "graded" control by the response-produced feedback. Such stimulation, produced by meeting schedule requirements, may have graded or continuous properties similar to some dimensions of exteroceptive stimuli (see Hobson, 1975;Pliskoff & Goldiamond, 1966;Rilling & McDiarmid, 1965). Hence, we used three sample-specific response requirements (FR 3,FR A symbolic matching-to-sample task was used in the present experiments because some data in Cohen et al (1976) and data presented by Ruhl and Paul (Note 1) suggested that in an identity matching task, with different schedule requirements for the different samples, an early preference is induced for those comparison hues that have the more favorable schedule when they appear as the sample (i.e., a low ratio required to a particular sample hue increases the likelihood that that hue will be pecked when it appears as a comparison stimulus).…”
mentioning
confidence: 99%
“…Evidence indicates that some, as yet little understood, dimension of the FR schedule can function as a discriminative stimulus. Pigeons can' differentiate between two FRs of different sizes in the absence of any external stimuli correlated with each schedule (Hobson, 1975;Keehn & Bratbak, 1967;Pliskoff & Goldiamond, 1966).…”
Section: Western Washington State Couege Bellingham Washington98225mentioning
confidence: 99%
“…Evidence indicates that some, as yet little understood, dimension of the FR schedule can function as a discriminative stimulus. Pigeons can' differentiate between two FRs of different sizes in the absence of any external stimuli correlated with each schedule (Hobson, 1975;Keehn & Bratbak, 1967;Pliskoff & Goldiamond, 1966).Exteroceptive cues can also be correlated with FR schedules, and these cues have been shown to affect the pattern of responding maintained by the schedule. For example , lwaideh (1973) and Thomas (1964) both found that pigeons paused longer before the fust component of a three-component chained schedule than before the fIrst component of a three-component tandem schedule.…”
mentioning
confidence: 99%